Information Hiding Using Mosaic Images with Random Image Key Generation (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
Image watermarking is one of the efficient technique to send the secrete information from sender to receiver. The concept of information hiding using mosaic images is also an efficient technique of keeping the information secretes. The existing technique of information hiding using LSB based embedding of information and then using greedy search algorithm for the searching of images tile into the database. The technique implemented in the literature so far provides more error rate and also the time complexity is greater, since it uses the concept of greedy search for the searching of most similar image tile in the database. Our proposed technique does not require searching of the tile images resulting in a lower computational time. The proposed technique is based on the concept of watermarking, where the secrete image is converted into a number of tiles and then each of the tile image is converted into binary value. These binary values are used as a secrete key from which the cover image is encrypted and decrypted.